Fasting Effects on Emotion Changes – A Multi-Level Analyses - Mastor, Khairul Anwar; Locke, Kenneth; Kasan, Hasnan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: Psychological effects of a long term fasting has not yet been widely studied as compared to its medical and physiological effects. Little attention has been given to the psychological effects such as emotion due to fasting. Based on current emotion theories, emotion arouses and changes corresponding to the experience one undergoing. Ramadan fasting is a thirty day intermittent fasting which likely affects the emotion of those observing the fasting. In the present study, it was hypothesized that fasting may induce changes in positive and negative emotion throughout thirty days in RamadanMethodology: A total of 164 undergraduate students participated in the study (117 muslims who fast and 47 non-muslims as a control group - not fasting). A daily self-report on emotion was taken in separate three time periods – before, during and after Ramadan - among participants. A Mixed Model Analyses was used to analyze the pattern of emotion changes a week before, during and a week after Ramadan fasting periodResults: Emotion of jealousy was found to increase (b=.02) before Ramadan begins. During Ramadan, Happy and Joy increases (b=.008 and b=.010 respectively) while impatience, moody and sadness decrease (b=-.007, b= -.007 and b=-.007 respectively). A week after Ramadan ends, levels of happy and joy decrease (-0.008 and -.012) while levels of Fear, Impatience and Moody increase during the first week after Ramadan ends, respectively (b=.018, b=.006 and b =.002). There were also no significant interaction effects between day*gender and day*religion on the emotion mean scores.Applications/Originality/Value: Further studies are recommended to conduct face-to-face interviews and more specific time of emotion record and other possible correlates that might influence the pattern of emotion changes to enhance our understanding of the psychological benefits of religiously based fasting.